2021
DOI: 10.1039/d1ma00278c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(triethylene glycol methyl ether methacrylate) hydrogel as a carrier of phosphotungstic acid for acid catalytic reaction in water

Abstract: An H3PW12O40-polymer composite was synthesized from a mixture of triethylene glycol methyl ether metacrylate monomer, triethylene glycol dimethacrylate crosslinker, and H3PW12O40. The heteropoly acid molecules were trapped in the hydrogel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al (2018) reported Fe 3 O 4 nanoparticle-embedded porous hydrogel beads as catalysts for the Fenton reaction of methyl orange [31]. Zhu et al (2021) reported poly(triethylene glycol methyl ether methacrylate) hydrogels as carriers of phosphotungstic acid for acid catalytic reactions in water [122]. Tokuyama et al (2022) developed TiO 2 nanoparticle-loaded poly(NIPA) fibers for the adsorption and photocatalytic degradation of organic pollutants in aquatic media [123].…”
Section: Reaction Fieldmentioning
confidence: 99%
“…Zhang et al (2018) reported Fe 3 O 4 nanoparticle-embedded porous hydrogel beads as catalysts for the Fenton reaction of methyl orange [31]. Zhu et al (2021) reported poly(triethylene glycol methyl ether methacrylate) hydrogels as carriers of phosphotungstic acid for acid catalytic reactions in water [122]. Tokuyama et al (2022) developed TiO 2 nanoparticle-loaded poly(NIPA) fibers for the adsorption and photocatalytic degradation of organic pollutants in aquatic media [123].…”
Section: Reaction Fieldmentioning
confidence: 99%
“…Several studies have shown that POM /peptide gels and chitosan- POM hydrogels have significant underwater adhesive applications with self-healing, thermos-responsive, and antibacterial properties. The composite hydrogels made up of poly­(triethylene glycol methyl ethermethacrylate) have been successfully used to support tungsten-based POM as an acid catalyst for the hydrolysis of ethyl acetate having low leaching characteristics in water and significant efficient catalysis. Moreover, POM s and hydrogels synthesized through the coassembly of basic amino acids have shown significant photothermal and photochromic properties .…”
Section: Introductionmentioning
confidence: 99%